Energy Consumption and Economic Growth: Empirical Evidence for Sudan - Elfaki, Khalid Eltayeb; Poernomo, Adi; Anwar, Nurul; Ahmad, Abdul Aziz (International Journal of Energy Economics and Policy, 2018)
This paper examines the dynamic relationship between energy consumption and economic growth in Sudan covering period 1984-2014. Using the autoregressive distributed lag model (ARDL) cointegration approach. Gross fixed capital formation (K), Trade Openness (OP), and Urban population (URP) were included as control variables. The cointegration results provide evidence on the existence of long-run equilibrium relationship among the variables. In the long run energy consumption has negative impact on economic growth. In contrast, in the short run energy consumption shows different impacts at the level and first difference on economic growth this attributed to fluctuations in oil production and Secession of southern Sudan, which is consider the main source of petroleum resources. The implications of the study is that, energy conservation policy regarding oil and gas would lead to improve in economic growth in Sudan, the short run and long run plans of low-priced energy generation domestically to meet increasing energy demand is highly needed policy as well. Keywords: energy consumption, economic growth, autoregressive distributed lag model. JEL Classifications: Q43, F43, C19